Real-world use of bezlotoxumab to prevent recurrent infections: a single-center experience and meta-analysis - Kanika Sehgal; Parul Berry; Raseen Tariq; Darrell S. Pardi; Sahil Khanna (Therapeutic Advances in Gastroenterology)
Background: Clostridioides difficile infection (CDI) treated with bezlotoxumab (BEZ) has been demonstrated to have a lower recurrence rate than placebo in clinical trials. However, real-world data on BEZ’s effectiveness remain limited and heterogeneous. Objectives: To evaluate the real-world effectiveness of BEZ in preventing CDI recurrence through a single-center retrospective cohort and a meta-analysis. Design: A retrospective cohort study and a meta-analysis. Methods: A retrospective study of patients treated with BEZ from 2017 to 2021 was performed at the Mayo Clinic. Demographics, CDI diagnostics, and several prespecified risk factors were analyzed. A literature search was conducted in August 2024 utilizing the Cochrane Central Register of Controlled Trials, Embase, Medline, Scopus, and Web of Science Core Collection. Studies reporting CDI resolution rates with BEZ were included. The random-effects model described by DerSimonian and Laird was used to calculate weighted pooled resolution rates (WPR) with 95% confidence intervals (CI). We assessed heterogeneity with the inconsistency index ( I 2 ) statistic. Results: Across 28 studies and our retrospective cohort, 2639 CDI patients were analyzed. Among 1786 patients treated with BEZ, 1450 achieved clinical resolution (WPR: 81.6%, 95% CI 77.2–85.6%), with significant heterogeneity ( I ² = 77.3%). In subgroup analysis, the pooled relative risk of recurrence was 0.56 (95% CI 0.36–0.88; p  < 0.01) for BEZ with SoC compared to SoC alone. A WPR of 83.3% (95% CI 75.5%–91.1%) for patients receiving BEZ with SoC was observed when compared with a WPR of 70.8% (95% CI 62.7%–78.8%) in patients receiving SoC alone on subgroup analysis. In our cohort of 47 patients, the CDI resolution rate was 72.3% (34/47). Conclusion: Our retrospective study and meta-analysis demonstrate the real-world efficacy of BEZ in reducing CDI recurrence. The higher recurrence rates in our cohort likely reflect the high-risk nature of the population, including a greater proportion of immunocompromised patients.